Effect of Trash Addition to the Soil on Microbial Communities and Physico-Chemical Properties of Soils and Growth of Sugarcane Plants - Qing Liao; Guang-Po Wei; Gui-Fen Chen; Bin Liu; Dong-Liang Huang; Yang-Rui Li (Sugar Tech, 2014)

A poplar R2R3-MYB transcription factor, PtrMYB152, is involved in regulation of lignin biosynthesis during secondary cell wall formation - Chaofeng Li; Xianqiang Wang; Wanxiang Lu; Rui Liu; Qiaoyan Tian; Yiming Sun; Keming Luo (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Investigation on Etiology of Hepatic Venous Obstruction Budd-Chiari Syndrome - Zhi-Long Tian; Gao-Lei Jia; Hai-Lin Xi; Su Feng; Xiao-Kai Wang; Rui Li (Cell Biochemistry and Biophysics, 2014)

Detection and Analysis of 12 Heavy Metals in Blood and Hair Sample from a General Population of Pearl River Delta Area - Jiqiang Li; Dongzhi Cen; Donglan Huang; Xufeng Li; Jiajun Xu; Shilin Fu; Rui Cai; Xiaocong Wu; Ming Tang; Yao Sun; Jiren Zhang; Jingfen Zheng (Cell Biochemistry and Biophysics, 2014)

Advances in investigations on the mechanism of cancer multidrug resistance and the liposomes-based treatment strategy - Fan Zeng; Rui-Jun Ju; Xue-Tao Li; Wan-Liang Lu (Journal of Pharmaceutical Investigation, 2014)

Structures and antiviral activities of butyrolactone derivatives isolated from Aspergillus terreus MXH-23 - Xinhua Ma; Tianjiao Zhu; Qianqun Gu; Rui Xi; Wei Wang; Dehai Li (Journal of Ocean University of China, 2014)

Spatial characteristics of development efficiency for urban tourism in eastern China: A case study of six coastal urban agglomerations - Rui Li; Qian Guo; Dianting Wu; Hongmei Yin; Hua Zhang; Taoxing Zhu (Journal of Geographical Sciences, 2014)

Isolation of α-glucosidase inhibitors including a new flavonol glycoside from Dendrobium devonianum - Jing Sun; Fudong Zhang; Miao Yang; Junjie Zhang; Lijun Chen; Rui Zhan; Ling Li; Yegao Chen (Natural Product Research, 2014)

Antibacterial activities of nemonoxacin against clinical isolates of Staphylococcus aureus: an in vitro comparison with three fluoroquinolones - Zhaoxia Li; Youning Liu; Rui Wang; Aimin Li (World Journal of Microbiology and Biotechnology, 2014)

A down-regulated epi-allele of the genomes uncoupled 4 gene generates a xantha marker trait in rice - Rui-Qing Li; Jian-Zhong Huang; Hai-Jun Zhao; Hao-Wei Fu; You-Fa Li; Guo-Zhen Liu; Qing-Yao Shu (Theoretical and Applied Genetics, 2014)

Edge biomarkers for classification and prediction of phenotypes - Tao Zeng; WanWei Zhang; XiangTian Yu; XiaoPing Liu; MeiYi Li; Rui Liu; LuoNan Chen (Science China Life Sciences, 2014)

A thinned lithosphere beneath coastal area of southeastern China as evidenced by seismic receiver functions - Zhuo Ye; QiuSheng Li; Rui Gao; HongShuang Zhang; RiZheng He; HaiYan Wang; WenHui Li (Science China Earth Sciences, 2014)

Rheological Characteristics of Weak Rock Mass and Effects on the Long-Term Stability of Slopes - Tianhong Yang; Tao Xu; Hongyuan Liu; Chunming Zhang; Shanyong Wang; Yongqin Rui; Li Shen (Rock Mechanics and Rock Engineering, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

FEM application to loess slope excavation and support: case study of Dong Loutian coal bunker, Shuozhou, China - Zhi Qing Li; Ibrahim Adewuyi Oyediran; Chuan Tang; Rui Lin Hu; Ying Xin Zhou (Bulletin of Engineering Geology and the Environment, 2014)

Association between serum sulfatide and carotid intima media thickness in patients with familial hypercholesterolemia - Gang Li; Rui Hu (Glycoconjugate Journal, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

A new naphthol from the twigs and leaves of Pterospermum yunnanense - Haoliang Li; Guoli Huang; Bo Liu; Ying Liu; Rui Zhan; Yegao Chen (Natural Product Research, 2014)

Piromelatine exerts antinociceptive effect via melatonin, opioid, and 5HT1A receptors and hypnotic effect via melatonin receptors in a mouse model of neuropathic pain - Yuan-Yuan Liu; Dou Yin; Li Chen; Wei-Min Qu; Chang-Rui Chen; Moshe Laudon; Neng-Neng Cheng; Yoshihiro Urade; Zhi-Li Huang (Psychopharmacology, 2014)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

Production of low phytic acid rice by hairpin RNA- and artificial microRNA-mediated silencing of OsMIK in seeds - Wen-Xu Li; Jian-Zhong Huang; Hai-Jun Zhao; Yuan-Yuan Tan; Hai-Rui Cui; Yves Poirier; Qing-Yao Shu (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Cassiterite LA-MC-ICP-MS U/Pb and muscovite 40Ar/39Ar dating of tin deposits in the Tengchong-Lianghe tin district, NW Yunnan, China - Xiao-Cui Chen; Rui-Zhong Hu; Xian-Wu Bi; Hui-Min Li; Jiang-Bo Lan; Cheng-Hai Zhao; Jing-Jing Zhu (Mineralium Deposita, 2014)

Characteristics of UV radiation at Tazhong of the Tarim Basin, west China - Lili Jin; Qing He; Zhenjie Li; Rui Liu; Ali Mamtimin; Qilong Miao (Meteorology and Atmospheric Physics, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Microseismic monitoring of columnar jointed basalt fracture activity: a trial at the Baihetan Hydropower Station, China - Bing-Rui Chen; Qing-Peng Li; Xia-Ting Feng; Ya-Xun Xiao; Guang-Liang Feng; Lian-Xing Hu (Journal of Seismology, 2014)

Upregulation of EHD2 after Intracerebral Hemorrhage in Adult Rats - Kaifu Ke; Ying Rui; Lei Li; Heyi Zheng; Wei Xu; Xiang Tan; Jianhua Cao; Xiaoyan Wu; Gang Cui; Maohong Cao (Journal of Molecular Neuroscience, 2014)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

A new algorithm for fine acquisition of GPS carrier frequency - Kedong Wang; Rui Jiang; Yong Li; Ning Zhang (GPS Solutions, 2014)

Anti-depressive activities and biotransformation of timosaponin B-III and its derivatives - WeiXin Jiang; Jing Guo; Rui Xue; KaiCheng Zhu; ZhiXiong Li; MingCang Chen; ChengGang Huang (Natural Product Research, 2014)

Zircon U–Pb geochronology and geochemistry of the Maoliger quartz monzodiorites, Inner Mongolia, China: implications for Carboniferous arc magmatism and closure of the Palaeo-Asian Ocean - Li-Min Wang; Xiao-Guo Chi; Zhi Zhao; Wei Sun; Rui Zhang; Shi-Yu Pan; Jing-Yu Quan (International Geology Review, 2014)

Daytime precipitation identification scheme based on multiple cloud parameters retrieved from visible and infrared measurements - XianTong Liu; Qi Liu; YunFei Fu; Rui Li (Science China Earth Sciences, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

A thermo-halo-tolerant and proteinase-resistant endoxylanase from Bacillus sp. HJ14 - Junpei Zhou; Qian Wu; Rui Zhang; Minghe Mo; Xianghua Tang; Junjun Li; Bo Xu; Junmei Ding; Qian Lu; Zunxi Huang (Folia Microbiologica, 2014)

Degradation of recalcitrant aliphatic and aromatic hydrocarbons by a dioxin-degrader Rhodococcus sp. strain p52 - Hai-Yan Yang; Rui-Bao Jia; Bin Chen; Li Li (Environmental Science and Pollution Research, 2014)

Ecto-Mesenchymal Stem Cells from Facial Process: Potential for Muscle Regeneration - Xin Nie; Yongjun Xing; Manjin Deng; Li Gang; Rui Liu; Yongjie Zhang; Xiujie Wen (Cell Biochemistry and Biophysics, 2014)

DNA Methylation: Roles in Rheumatoid Arthritis - Feng-Lai Yuan; Xia Li; Rui-Sheng Xu; Dong-Lin Jiang; Xiao-Gang Zhou (Cell Biochemistry and Biophysics, 2014)

Clinical Factors Associated With the Diagnosis and Progression of Diabetic Nephropathy - Shuang Liang; Qian Li; Han-Yu Zhu; Jian-Hui Zhou; Rui Ding; Xiang-Mei Chen; Guang-Yan Cai (Cell Biochemistry and Biophysics, 2014)

Distinctive expression and cellular distribution of dopamine receptors in the pancreatic islets of rats - Ye Chen; Feng Hong; Hui Chen; Rui-Fang Fan; Xiao-Li Zhang; Yue Zhang; Jin-Xia Zhu (Cell and Tissue Research, 2014)

Bernoulli-based random undersampling schemes for 2D seismic data regularization - Rui Cai; Qun Zhao; De-Ping She; Li Yang; Hui Cao; Qin-Yong Yang (Applied Geophysics, 2014)

Simultaneous inversion of petrophysical parameters based on geostatistical a priori information - Xing-Yao Yin; Rui-Ying Sun; Bao-Li Wang; Guang-Zhi Zhang (Applied Geophysics, 2014)

High-resolution modeling study of the Kuroshio path variations south of Japan - Rui Li; Zuowei Zhang; Lixin Wu (Advances in Atmospheric Sciences, 2014)

Assessment of dietary phytoestrogen intake via plant-derived foods in China - Xiao Juan Hu; Wan Rui Song; Li Ying Gao; Shao Ping Nie; Gerhard Eisenbrand; Ming Yong Xie (Food Additives & Contaminants: Part A, 2014)

Thermal comfort and tourism climate changes in the Qinghai–Tibet Plateau in the last 50 years - Rui Li; Xiaoli Chi (Theoretical and Applied Climatology, 2014)

How do soil and water conservation practices influence climate change impacts on potato production? Evidence from eastern Canada - Thomas O. Ochuodho; Edward Olale; Van A. Lantz; Jerome Damboise; Jean-Louis Daigle; Fan-Rui Meng; Sheng Li; T. Lien Chow (Regional Environmental Change, 2014)

The transcriptional response of apple alcohol acyltransferase (MdAAT2) to salicylic acid and ethylene is mediated through two apple MYB TFs in transgenic tobacco - Peng-Cheng Li; Shao-Wei Yu; Jin Shen; Qing-Qing Li; Da-Peng Li; De-Quan Li; Cheng-Chao Zheng; Huai-Rui Shu (Plant Molecular Biology, 2014)

Two new species of Spadicoides and Gangliostilbe from southern China - Li-Guo Ma; Ji-Wen Xia; Ying-Rui Ma; Rafael F. Castañeda-Ruíz; Xiu-Guo Zhang (Mycological Progress, 2014)

Effect of hepatic function on the EC50 of midazolam and the BIS50 at the time of loss of consciousness - Yu-hong Li; Rui He; Jin-guang Ruan (Journal of Zhejiang University-SCIENCE B, 2014)

Seed-specific silencing of OsMRP5 reduces seed phytic acid and weight in rice - Wen-Xu Li; Hai-Jun Zhao; Wei-Qin Pang; Hai-Rui Cui; Yves Poirier; Qing-Yao Shu (Transgenic Research, 2014)

Phylogenetic relationships between Leymus and related diploid Triticeae species revealed by ISSR markers - Guo-Ye Guo; Rui-Wu Yang; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Fang Chen; Sheng-Hua Wang (Biologia, 2014)

Streptomyces calidiresistens sp. nov., isolated from a hot spring sediment - Yan-Yan Duan; Hong Ming; Lei Dong; Yi-Rui Yin; Yi Zhang; En-Min Zhou; Lan Liu; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Permeability Comparison between Hepatocyte and Low Efflux MDCKII Cell Monolayer - Rui Li; Yi-An Bi; Yurong Lai; Kiyohiko Sugano; Stefanus J. Steyn; Patrick E. Trapa; Li Di (The AAPS Journal, 2014)

Molecular cloning and expression analysis of mannose receptor in blunt snout bream (Megalobrama amblycephala) - Xiaoling Liu; Xiaocheng Tang; Li Wang; Jie Li; Hong Wang; Shun Wei; Rui Fang; Wei Ji; Gailing Yuan; Nan Chen; Zemao Gu; Xueqin Liu; et al. (Molecular Biology Reports, 2014)

RETRACTED ARTICLE: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Expression of bone morphogenetic protein 2, 4, and related components of the BMP signaling pathway in the mouse uterus during the estrous cycle - Yan Li; Quan-wei Wei; Jian-gang Feng; Mu-lin Xu; Rui-hua Huang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2014)

Seohaeicola westpacificensis sp. nov., A Novel Member of Genera Seohaeicola Isolated from Deep West Pacific Sea Water - Shuhui Xian; Rui Zhang; Jia Sun; Yi Chen; Wenchao Deng; Shuhui Li; Nianzhi Jiao (Current Microbiology, 2014)

Protective Effects of Selenium on Mercury Induced Immunotoxic Effects in Mice by Way of Concurrent Drinking Water Exposure - Xuan Li; Daqiang Yin; Jiang Li; Rui Wang (Archives of Environmental Contamination and Toxicology, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

The effect of NF-κB antisense oligonucleotide on transdifferentiation of fibroblast in lung tissue of mice injured by bleomycin - Yan Zhou; Xiaoye Zhang; Mingqi Tan; Rui Zheng; Li Zhao (Molecular Biology Reports, 2014)

A “middle-out” approach to human pharmacokinetic predictions for OATP substrates using physiologically-based pharmacokinetic modeling - Rui Li; Hugh A. Barton; Phillip D. Yates; Avijit Ghosh; Angela C. Wolford; Keith A. Riccardi; Tristan S. Maurer (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Purification and photodynamic bioactivity of phycoerythrin and phycocyanin from Porphyra yezoensis Ueda - Chuner Cai; Yuan Wang; Chunxia Li; Ziye Guo; Rui Jia; Weining Wu; Yan Hu; Peimin He (Journal of Ocean University of China, 2014)

Shoot regeneration and cryopreservation of shoot tips of apple (Malus) by encapsulation–dehydration - Bai-Quan Li; Chao-Hong Feng; Ling-Yun Hu; Min-Rui Wang; Long Chen; Qiao-Chun Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

Calculation of saturation in carbonate reservoirs based on electrical efficiency - Xiong-Yan Li; Rui-Bao Qin; Chun-Cheng Liu; Zhi-Qiang Mao (Applied Geophysics, 2014)

An automatic seismic signal detection method based on fourth-order statistics and applications - Xi-Qiang Liu; Yin Cai; Rui Zhao; Yin-Gang Zhao; Bao-An Qu; Zhi-Jun Feng; Hong Li (Applied Geophysics, 2014)

Expression and roles of As-NUPR1 protein from Artemia sinica during embryo development and in response to salinity stress - Rui Zhang; Feng Yao; Cheng Cheng; Yifei Chen; Ying Lv; Zengrong Li; Na Zhao; Ting Wang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Down-regulated Six2 by knockdown of neurofibromin results in apoptosis of metanephric mesenchyme cells in vitro - Puhui Zhou; Tielin Chen; Yin Fang; Honglian Wang; Mi Li; Pengpeng Ma; Lu He; Qianyin Li; Tianming Liu; Xianggui Yang; Fang Nie; Xiaoyan Wang; et al. (Molecular and Cellular Biochemistry, 2014)

Assessment of combined antiandrogenic effects of binary parabens mixtures in a yeast-based reporter assay - Dehua Ma; Lujun Chen; Xiaobiao Zhu; Feifei Li; Cong Liu; Rui Liu (Environmental Science and Pollution Research, 2014)

Endophytic nitrogen-fixing Klebsiella variicola strain DX120E promotes sugarcane growth - Chun-Yan Wei; Li Lin; Li-Jing Luo; Yong-Xiu Xing; Chun-Jin Hu; Li-Tao Yang; Yang-Rui Li; Qianli An (Biology and Fertility of Soils, 2014)

Expression patterns of prdm1 during chicken embryonic and germline development - Zhiyi Wan; Lei Rui; Zandong Li (Cell and Tissue Research, 2014)

Tropomyosin-related kinase B promotes distant metastasis of colorectal cancer through protein kinase B-mediated anoikis suppression and correlates with poor prognosis - Meng Fan; Jianyong Sun; Wei Wang; Jing Fan; Lei Wang; Xiang Zhang; Angang Yang; Weizhong Wang; Rui Zhang; Jipeng Li (Apoptosis, 2014)

Roseomonas alkaliterrae sp. nov., isolated from an alkali geothermal soil sample in Tengchong, Yunnan, south-west China - Lei Dong; Hong Ming; Yi-Rui Yin; Yan-Yan Duan; En-Min Zhou; Guo-Xing Nie; Hui-Geng Feng; Lan Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Involvement of Protease-Activated Receptor 2 in Nociceptive Behavior in a Rat Model of Bone Cancer - Yanju Bao; Baojin Hua; Wei Hou; Zhan Shi; Weidong Li; Conghuang Li; Cihui Chen; Rui Liu; Yinggang Qin (Journal of Molecular Neuroscience, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

Static corrections methods in the processing of deep reflection seismic data - Xiaosan Zhu; Rui Gao; Qiusheng Li; Ye Guan; Zhanwu Lu; Haiyan Wang (Journal of Earth Science, 2014)

Monitoring and modeling the effects of groundwater flow on arsenic transport in Datong Basin - Qian Yu; Yanxin Wang; Rui Ma; Chunli Su; Ya Wu; Junxia Li (Journal of Earth Science, 2014)

Erratum to: Coralslurrinella hongkonensis gen. nov., sp. nov., a novel bacterium in the family Psychromonadaceae, isolated from the coral Platygyra carnosus - Yanxia Li; Yuki Chan; Yingnan Fu; Rui Zhang; Jill M. Y. Chiu (Antonie van Leeuwenhoek, 2014)

Zhizhongheella caldifontis gen. nov., sp. nov., a novel member of the family Comamonadaceae - Lei Dong; Hong Ming; Lan Liu; En-Min Zhou; Yi-Rui Yin; Yan-Yan Duan; Guo-Xing Nie; Hui-Geng Feng; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Irregular western margin of the Yangtze block as a cause of variation in tectonic activity along the Longmen Shan fault zone, eastern Tibet - Xiaoyu Guo; G. Randy Keller; Rui Gao; Xiao Xu; Haiyan Wang; Wenhui Li (International Geology Review, 2014)

Two new compounds from a marine-derived fungus Penicillium oxalicum - Pei-Le Wang; Dan-Yi Li; Lei-Rui Xie; Xin Wu; Hui-Ming Hua; Zhan-Lin Li (Natural Product Research, 2014)

The Neuroprotective Effects of Isoflurane Preconditioning in a Murine Transient Global Cerebral Ischemia–Reperfusion Model: The Role of the Notch Signaling Pathway - Hao-peng Zhang; Yan-yan Sun; Xiao-mei Chen; Li-bang Yuan; Bin-xiao Su; Rui Ma; Rui-ni Zhao; Hai-long Dong; Lize Xiong (NeuroMolecular Medicine, 2014)

Synthesis and antitumor activity evaluation of 2-arylisoquinoline-1,3(2H,4H)-diones in vitro and in vivo - Bo-Rui Kang; Juan Wang; Huan Li; Yan Li; Qi-Bing Mei; San-Qi Zhang (Medicinal Chemistry Research, 2014)

Selection and Characterization of a Peptide Specifically Targeting to Gastric Cancer Cell Line SGC-7901 Using Phage Display - Han Wang; Rui Li; Caixia Ma; Shaoying Lu; Dan Zhang; Yonge Guo; ChunYan Li; Jinling Wu; Qixuan Wang; Jinhui Xu; Yanyan Hu; Yuen Liu; et al. (International Journal of Peptide Research and Therapeutics, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Impacts of Transportation Routes on Landscape Diversity: A Comparison of Different Route Types and Their Combined Effects - Shiliang Su; Rui Xiao; Delong Li; Yi’na Hu (Environmental Management, 2014)

An Endophytic Sanguinarine-Producing Fungus from Macleaya cordata, Fusarium proliferatum BLH51 - Xue-Jun Wang; Chang-Li Min; Mei Ge; Rui-Hua Zuo (Current Microbiology, 2014)

Plant diversity as a good indicator of vegetation stability in a typical plateau wetland - Wei Li; Rui Tan; Yu-ming Yang; Juan Wang (Journal of Mountain Science, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

Construction, characterization and expression of full length cDNA clone of sheep YAP1 gene - Wei Sun; Da Li; Rui Su; Hassan H. Musa; Ling Chen; Hong Zhou (Molecular Biology Reports, 2014)

MicroRNA-128 regulates the differentiation of rat bone mesenchymal stem cells into neuron-like cells by Wnt signaling - Rui Wu; Yue Tang; Wenqiao Zang; Yuanyuan Wang; Min Li; Yuwen Du; Guoqiang Zhao; Yuming Xu (Molecular and Cellular Biochemistry, 2014)

The expression of Apoc3 mRNA is regulated by HNF4α and COUP-TFII, but not acute retinoid treatments, in primary rat hepatocytes and hepatoma cells - Meredith Howell; Rui Li; Rui Zhang; Yang Li; Wei Chen; Guoxun Chen (Molecular and Cellular Biochemistry, 2014)

Molecular dynamics-based self-organizing molecular field analysis on 3-amino-6-arylpyrazines as the ataxia telangiectasia mutated and Rad3 related (ATR) protein kinase inhibitors - Hao Luo; Jianyou Shi; Lufei Lu; Feng Wu; Meng Zhou; Xueyan Hou; Wenjuan Zhang; Zhengyu Ding; Rui Li (Medicinal Chemistry Research, 2014)

Converting natural vegetation to farmland alters functional structure of ground-dwelling beetles and spiders in a desert oasis - Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Bo-Wen Jin; Li-Juan Chen (Journal of Insect Conservation, 2014)

Extracellular DNA Inhibits Salmonella enterica Serovar Typhimurium and S. enterica Serovar Typhi Biofilm Development on Abiotic Surfaces - Hu Wang; Yang Huang; Shuyan Wu; Yuanyuan Li; Ying Ye; Yajie Zheng; Rui Huang (Current Microbiology, 2014)

The role of Somatic embryogenesis receptor-like kinase 1 in controlling pollen production of the Gossypium anther - Ya-li Shi; San-dui Guo; Rui Zhang; Zhi-gang Meng; Mao-zhi Ren (Molecular Biology Reports, 2014)

Cloning and expression patterns of the brine shrimp (Artemia sinica) glycogen phosphorylase (GPase) gene during development and in response to temperature stress - Na Zhao; Ming Hou; Ting Wang; Yifei Chen; Ying Lv; Zengrong Li; Rui Zhang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Lack of association between the polymorphisms of hypoxia-inducible factor 1A (HIF1A) gene and SLE susceptibility in a Chinese population - Chen-Chen Feng; Qian-Ling Ye; Yan Zhu; Rui-Xue Leng; Gui-Mei Chen; Jie Yang; Han Cen; Xiao-Ke Yang; Rui Li; Wang-Dong Xu; Hai-Feng Pan; Dong-Qing Ye (Immunogenetics, 2014)